Consumer good search: Theory and evidence - Saman Darougheh (Danmarks Nationalbank, 2021)
I develop a model of the consumer good market where the individual's search decision is consistent with balanced-growth preferences. Here, optimal search is independent of income but increases with the time endowment. I characterize the potentially multiple equilibria and test whether the model can replicate differences in observed shopping behavior between employed and unemployed individuals. I use the American Time Use Survey to show that unemployed individuals have almost 50% more time available for leisure and shopping and spend 27% more time shopping than the employed. In the calibrated model, however, unemployed individuals will spend around twice as much time shopping as employed individuals. I argue that micro founded goods search models are not yet ready for business cycle analysis and discuss ways of reconciling the model with the data.
Keywords: D11; E21; E32; L11; 330; Research; households